Exploring the challenges in the management of childhood pneumonia-qualitative findings from health care providers from two high prevalence states in India - Rani Mohanraj; Shuba Kumar; Monica Agarwal; Bhavna Dhingra; Saradha Suresh (PLOS Global Public Health, 2022)
India ranks among the top five countries in the world in child deaths due to pneumonia. Apart from poor public awareness, inadequate health infrastructure and treatment services have compromised effective management. This qualitative study guided by components of the Andersen-Newman’s health care utilization framework explored contextual and community challenges faced by health care providers (HCPs) in the delivery of care services for children with pneumonia in select districts of Uttar Pradesh (UP) and Madhya Pradesh (MP). Semi structured interviews (SSIs) and focus groups discussions (FGDs) were carried out with a purposive sample of HCPs selected from three districts in each state. The HCPs included doctors and community health workers (CHWs). All SSIs and FGDs were audio- recorded, with consent, transcribed verbatim, entered into NVivo and analysed using thematic analysis. A total of 15 SSIs were conducted with doctors and eight FGDs were carried out with CHWs. Two themes that best explained the data were:, 1. Health systems: barriers faced in delivery of care services and 2. Evaluated Need: perceptions on community awareness and practices. According to the HCPs inadequacies in government health infrastructure both manpower and equipment, and skill deficits of paramedical staff and CHWs contributed to poor quality of care services for management of childhood pneumonia. This combined with inadequate understanding of pneumonia in the community, dependence on unqualified care providers and distrust of government hospitals acted as barriers to seeking appropriate medical care. Additionally, poor compliance with exclusive breast feeding practices, nutrition and hygiene had contributed to the high prevalence of the disease in these states. Strengthening public health facilities, instilling trust and confidence in people about the availability and the quality of these services and enhancing health literacy around childhood pneumonia would be critical towards protecting children from this disease.